Computer-aided simulation of a vertical-axis wind turbine. Issue 4 (8th December 2020) - Yigit, Cemil
Abstract : In many studies, computer-aided simulation methods are used to design vertical-axis wind turbines. Compared with conventional optimization methods, computer-aided optimization methods, which show continuous improvement in parallel with technology, provide important advantages, particularly in terms of time and cost. On the one hand, a wind turbine is designed to obtain maximum power; on the other hand, this design must be able to operate safely under extreme conditions. When considered from this point of view, computational fluid dynamic analysis is the first step that provides input to structural analysis, and the accuracy of the structural analysis is directly related to the accuracy of the computational fluid dynamic analysis. In this study, the fluid–structure interaction method of the H-type Darrieus wind turbine was carried out. The computational fluid dynamic model was confirmed by experimental data in the literature. The results showed that the six-degrees-of-freedom solver deviates on average 5.0% less than experimental data. Using the fluid–structure interaction method, the maximum principal stress, equivalent stress and deformation values on the blade were obtained depending on the pressure load distribution on the turbine blade, and it was determined that the turbine can operate safely under operating conditions.